Energy Efficiency of Air Conditioners in Developing Countries: A Malaysian Case Study - Fatihah Salleh S.; Mohd Isa A.; Eqwan Roslan M.; Ab Rashid Tuan Abdullah T. (Institute of Physics Publishing, 2023)
Air conditioning; Climate change; Developing countries; Domestic appliances; Emission control; Energy utilization; Greenhouse gases; CO2 emission reduction; Electricity saving; Emissions reduction; Energy performance; inverter; Minimum energy; Reduce energy consumption; Technical database; Energy efficiency